(untitled) (Nigerian Journal of Physiological Sciences, 2021)
Summary: Pain serves a protective function and is often lost in chronic conditions such as painful diabetic neuropathy (PDN). This has been reported to be associated with ongoing inflammation. This study aims to investigate an association between body immune responses, neutrophil-lymphocyte ratio (NLR) and pain perception in DPN patients. Sixty volunteers were recruited for the study. 30 control and 30 diagnosed DPN patients (used Biothesiometer). All subjects were trained and informed consents were obtained. The pain threshold was significantly (p<0.05) lower in DPN (23.48±1.19 sec) compared to control group (30.38±1.9 sec), there was significant lower NLR in DPN (1.27±0.09) compared to control group (1.93±0.1) and the serum level of IL6 (15.31±0.85 pg/ml) in DPN was significantly higher compared to control group (11.9±0.15 pg/ml), likewise the serum level of IL10 (13.26±2.78 pg/ml) in DPN is significantly higher compared to control group (6.59±1.07 pg/ml). This study showed that hyperalgesia seen in patients with DPN was independent of increased NLR, and increased IL6 & IL10 seen in this group of patients indicates need to further explore the role of immunological response in the pathogenesis and progression of DPN.